On (α,β)-Derivations in BCI-Algebras - G. Muhiuddin; Abdullah M. Al-Roqi (Discrete Dynamics in Nature and Society)
The notion of (regular) (α,β)-derivations of a BCI-algebra X is introduced, some useful examples are discussed, and related properties are investigated. The condition for a (α,β)-derivation to be regular is provided. The concepts of a d(α,β)-invariant (α,β)-derivation and α-ideal are introduced, and their relations are discussed. Finally, some results on regular (α,β)-derivations are obtained.